Histological Observation Of Milkfish Organs With Stunting Phenomenon - Aris, Muhammad; Malan, Sudirto (Jurnal Ilmiah Platax, 2021)
Milkfish (Chanos chanos) is an important economic fish. Milkfish is widely consumed because it has high nutritional value. Milkfish is also used as live bait for fishing. In the milkfish cultivation system, increasing production is a very important factor. One of the efforts to increase production in fish farming systems is the application of high stocking density. Constraints to the application of the high stocking density cause the growth of milkfish to be non-uniform, some of them even experience stunting, which is a condition in which the fish experience slow growth. This study aims to observe the condition of the milkfish tissue with normal growth and stunted fish. Milkfish (Chanos chanos) used are fish that have been reared for 6 months. Fish organs that were sampled for observation were stunted and normal (non-stunting) fish. The organs observed were the gills, muscles, and intestines. The results showed that stunted milkfish (Chanos chanos) affected the condition of the gill tissue, muscles, and intestines. The gills are edema and necrosis. Muscles undergo edema, degeneration of muscle fibers, and necrosis. The intestine experiences necrosis or cell death.Keywords: Milkfish; Stunting; Histology.AbstrakIkan Bandeng (Chanos chanos) merupakan ikan bernilai ekonomis penting. Ikan Bandeng banyak dikonsumsi karena mempunyai nilai gizi yang tinggi. Ikan bandeng juga dimanfaatkan sebagai umpan hidup untuk penangkapan ikan. Pada sistem budidaya ikan Bandeng peningkatan produksi menjadi faktor yang sangat penting. Salah satu upaya peningkatan produksi pada sistem budidaya ikan adalah dengan aplikasi padat tebar yang tinggi. Kendala penerapan padat penebaran yang tinggi menyebabkan pertumbuhan ikan Bandeng tidak seragam, bahkan beberapa diantaranya mengalami stunting yang merupakan suatu kondisi dimana ikan mengalami lambatnya pertumbuhan. Penelitian ini, bertujuan untuk mengamati kondisi jaringan ikan bandeng dengan pertumbuhan normal dan ikan yang mengalami stunting. Ikan Bandeng (Chanos chanos) yang digunakan adalah ikan yang telah dipelihara selama 6 bulan. Organ ikan yang menjadi sampel pengamatan adalah ikan yang mengalami stunting dan normal (non-stunting). Organ yang diamati adalah insang, otot, dan usus. Hasil penelitian menunjukan ikan Bandeng (Chanos chanos) yang mengalami stunting mempengaruhi kondisi jaringan insang, otot dan usus. Insang mengalami edema dan necrosis. Otot mengamali edema, degenerasi serabut otot, dan necrosis. Usus mengalami necrosis atau kematian sel.Kata kunci: Ikan Bandeng, Stunting, Histologi